2006
DOI: 10.1007/s11239-006-9014-7
|View full text |Cite
|
Sign up to set email alerts
|

Platelet count, mean platelet volume, platelet distribution width, and plateletcrit do not correlate with optical platelet aggegation responses in healthy volunteers

Abstract: As a result, we found no correlation between platelet aggregation responses obtained with optical method and platelet indices proposed as indicators of certain pathologic conditions, and it does not seem possible to use platelet indices as a direct indicator of platelet activation. In conditions where platelet functions should have been assessed, platelet indices alone are inappropriate and further evaluation is necessary with different methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
92
5
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(101 citation statements)
references
References 21 publications
1
92
5
3
Order By: Relevance
“…In healthy human subjects, no correlation was identifi ed between PCT, MPV or PDW values and platelet aggregation results 54 ; however, these relationships could be modifi ed in the presence of infl ammation.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In healthy human subjects, no correlation was identifi ed between PCT, MPV or PDW values and platelet aggregation results 54 ; however, these relationships could be modifi ed in the presence of infl ammation.…”
Section: Discussionmentioning
confidence: 92%
“…Thus, platelets with a higher MPV are expected to be present in autoimmune thrombocytopenia when megakaryocytic stimulation is present. Conversely, platelets with a lower MPV are expected in thrombocytopenic states associated with marrow hypoplasia or aplasia 54 . Interestingly, 83% of the patients studied had normal MPV, and it appears that neither of these two mechanisms associated with thrombocytopenia was signifi cantly activated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many previous studies have demonstrated that platelets have large and variable sizes as can be observed in several clinical conditions, such as hemorrhage and myeloproliferative disorders. The increase may also indicate microvascular dysfunction (Beyan et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, LTA is only available at specialized laboratories [4]. Beyan et al mentions that although it implicitly shows the hemostatic function of platelets, LTA isn't routinely used; it is also a very expensive test [5].…”
mentioning
confidence: 99%